Analisis Faktor yang Memengaruhi Kinerja Perawat Terhadap Pelayanan Kesehatan Penyakit Tidak Menular dan Penyakit Menular di UPT Puskesmas Kuala (Lembaga Pengembangan Kinerja Dosen, 2026)
Health workers contribute up to 80% to the success of health development. For this reason, effective employee performance management is needed according to service performance for communicable and non-communicable diseases. The aim of this research is to analyze the factors that influence the performance of nurses in health services for non-communicable diseases and infectious diseases at the UPT Puskesmas Kuala, Kuala District, Langkat Regency.The research design used was an analytical survey with a cross sectional approach. The population of this study were all 31 nurses with a sample using a total sampling technique of 31 people. The data analysis used is the binary logistic regression test.The research results show that ability has a sig-p value of 0.025, attitude sig-p 0.014, learning sig-p 0.036, motivation sig-p 0.022, leadership sig-p 0.031 and work environment sig-p 0.048, which means it has an influence on nurse performance , while age sig-p 1.000 and perception sig-p 0.496 have no influence on nurse performance. Attitude is the dominant factor with an OR value of 28.446. In conclusion, ability, attitude, learning, motivation, leadership, and work environment influence nurse performance, while age and perception have no effect. Attitude is the most dominant factor influencing nurse performance.